Different Class Citizens: Understanding the Relationship between Socio-economic Inequality and Voting Abstention - Ehs Tamara (Sciendo, 2021)
In most established democracies the turnout gap along class lines has increased substantially since the 1980s. Political participation has become a question of resources: income, property, formal education, secure employment and overall social status determine citizens’ engagement in political decision-making. Using a mixed methods approach, our case-study shows that this also applies to Vienna – an overall rich city with a long tradition of social reform policies, often credited with the highest quality of life in the world. Although Vienna still has a relatively high turnout by international standards, political participation is very unevenly distributed once socio-economic resources are taken into account. Thereby and throughout life, class shapes people’s experiences with and as part of democracy. These experiences in turn have long-term effects on their trust in the political system and on their political self-efficacy. Our findings first and foremost contribute to the ongoing debate on democracy’s social imbalance and show that its consequences already apply on the regional level. The study additionally highlights the usefulness of mixed methods approaches when we aim at a better understanding of the class-based turnout gap.